2011
DOI: 10.1167/11.5.3
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and visual coding

Abstract: Visual coding is a highly dynamic process and continuously adapting to the current viewing context. The perceptual changes that result from adaptation to recently viewed stimuli remain a powerful and popular tool for analyzing sensory mechanisms and plasticity. Over the last decade, the footprints of this adaptation have been tracked to both higher and lower levels of the visual pathway and over a wider range of timescales, revealing that visual processing is much more adaptable than previously thought. This w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
308
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(321 citation statements)
references
References 243 publications
(287 reference statements)
12
308
0
1
Order By: Relevance
“…Adaptation, too, was found to induce changes of neuronal preferences in this cortical area (23,47). It is plausible that effects of adaptation and attention are mediated by the same neural circuits, even though the two processes are presumably governed by different constraints (48,49). Adaptation and attention can therefore manifest two strategies that nervous systems deploy over different temporal scales to achieve their unmatched versatility with limited resources.…”
Section: Discussionmentioning
confidence: 98%
“…Adaptation, too, was found to induce changes of neuronal preferences in this cortical area (23,47). It is plausible that effects of adaptation and attention are mediated by the same neural circuits, even though the two processes are presumably governed by different constraints (48,49). Adaptation and attention can therefore manifest two strategies that nervous systems deploy over different temporal scales to achieve their unmatched versatility with limited resources.…”
Section: Discussionmentioning
confidence: 98%
“…Studies using prolonged presentations have shown on the whole that the aftereffects last longer in migraine. Aftereffects could be a measure of the ability to adapt to a stimulus, and habituate the response, and it is unclear exactly which processes are involved in an aftereffect (9291), therefore more theoretically motivated experiments need to be designed before this can be assessed. It is possible that the time course of neural activity is actually the critical factor in migraine visual performance.…”
Section: Resultsmentioning
confidence: 99%
“…The processes underlying aftereffects can include neural fatigue, and possibly gain control, and have been reviewed (9291).…”
Section: Adaptation and Aftereffectsmentioning
confidence: 99%
“…Apart from the global-local processing already discussed, medical image perception must be reliant on additional processes such as the way the visual system adapts to images and consistent patterns of stimulation (Webster, 2011). For example, Webster and colleagues (Kompaniez-Dunigan, Abbey, Boone, & Webster, 2015) recently demonstrated that when pathology was easy to discriminate, encouraging adaptation of visual processes by repeated exposure did not increase detection performance.…”
Section: Discussionmentioning
confidence: 99%